O uso do jogo digital “batalha com dados” na aprendizagem de probabilidade nos anos iniciais do ensino fundamental - Iuly Kristina Silva Avelar (2023)
In this work we present research carried out in the Professional Master's Degree in Education and Teaching, at the Faculty of Education of the Federal University of Minas Gerais, in the 2nd semester of 2022. Despite having a curriculum in which statistical and probabilistic concepts must be inserted into the school reality since In the Early Years, we observed the difficulty that students have with reading and interpreting data, as well as with the use of probability in everyday situations. Aiming to analyze the learning process when using a digital game to teach Probability concepts to students in the 5th year of Elementary School, we carried out qualitative research, with the aim of valuing the description, dialogues and experiences of the students. To do this, we use filming, audio recording, photography, field diaries and written records as data production instruments. We are based on a Probabilistic Literacy model (Gal, 2005) and use the “game moments” indicated by Grando (2004), when developing intentional work with games in the classroom, to organize meetings. To carry out this research, and as a proposal for an Educational Resource, a digital game called by the students as “Batalha com Dados” was developed and, at the end, an e-book was organized, entitled “Probabilidados”, with some possible pedagogical interventions, the in order to help teachers use it. We conclude from the research that the game “Batalha com Dados” provides the opportunity for students to work collaboratively and encourages the development of social skills, such as communication and cooperation. By interacting with their colleagues during matches, they can discuss strategies, share knowledge and build a deeper understanding of Probability concepts together. However, it is important to emphasize that the use of the digital game does not replace the teacher's role. On the contrary, the teacher plays a fundamental role as mediator by contextualizing game activities, proposing reflections, asking questions and providing support to students. The game, therefore, should be used as a complementary resource to teaching, integrating with other pedagogical practices and teaching resources.